A synthetic human cytomegalovirus pp65-IE1 fusion antigen efficiently induces and expands virus specific T cells. Issue 38 (12th September 2017) - Link, Ellen K.; Brandmüller, Christine; Suezer, Yasemin; Ameres, Stefanie; Volz, Asisa; Moosmann, Andreas; Sutter, Gerd; Lehmann, Michael H.
Highlights: Generation of a recombinant MVA producing a novel HCMV pp65-IE1 fusion antigen. MVA-syn65_IE1 infected CD40B cells activate HCMV pp65- and IE1-specific T cells. MVA-syn65_IE1 induces pp65- and IE1-specific T cells in HHD mice. Abstract: Infection with human cytomegalovirus (HCMV) can cause severe complications in newborns and immunocompromised patients, and a prophylactic or therapeutic vaccine against HCMV is not available. Here, we generated a HCMV vaccine candidate fulfilling the regulatory requirements for GMP-compliant production and clinical testing. A novel synthetic fusion gene consisting of the coding sequences of HCMV pp65 and IE1 having a deleted nuclear localization sequence and STAT2 binding domain was introduced into the genome of the attenuated vaccinia virus strain MVA. This recombinant MVA, MVA-syn65_IE1, allowed for the production of a stable ∼120 kDa syn65_IE1 fusion protein upon tissue culture infection. MVA-syn65_IE1 infected CD40-activated B cells activated and expanded pp65- and IE1-specific T cells derived from HCMV-seropositive donors to at least equal levels as control recombinant MVA expressing single genes for pp65 or IE1. Additionally, we show that MVA-syn65_IE1 induced HCMV pp65- and IE1-epitope specific T cells in HLA-A2.1-/HLA-DR1- transgenic H-2 class I- / class II- knockout mice. Thus, MVA-syn65_IE1 represents a promising vaccine candidate against HCMV and constitutes a basis for the generation of a multivalent vaccine targeting relevant pathogens in immunocompromised patients.